Design of an E-Nose Detector for Contaminated Gas in Cow Farming Waste - Andrew Setiawan Rusdianto; Winda Amilia; Laila Adhani Putri Malik (International Journal on Food, Agriculture and Natural Resources, 2023)
Cattle farm waste is organic waste produced by the livestock industry in the form of feces and can emit gases that cause air pollution. Cow dung contamination can cause environmental problems, disturbing humans and livestock. Hazardous gases produced from the decomposition of livestock manure, namely methane (CH4), sulfur dioxide (SO2), ammonia (NH3), and hydrogen sulfide (H2S), can cause respiratory diseases, deplete ozone and contribute to the greenhouse effect. Based on these problems, measuring gas levels using an Electronic Nose (E-Nose) tool capable of detecting harmful gases in livestock pens is necessary. The E-nose is a device that mimics the human nose and consists of several gas sensors that can detect environmental odors. The design of the detection and measurement of toxic gases using an electronic nose in this study adopts the Internet of Things (IoT) concept using the Arduino Uno and ESP8266 microcontrollers and MQ-4, MQ-136, and MQ-137 gas sensors to read levels of pollutant gas in units of ppm with an average of 46.25 ppm for the MQ-4 sensor, 1.86 ppm for the MQ-136 sensor, and 4.97 ppm for the MQ-137. The sensors were subjected to functional tests consisting of validity testing, resulting in a calculated r value of 1, meaning that each gas sensor performs its measurement function correctly or validly. The reliability test of the MQ-4 sensor is 0.00, the MQ-136 sensor is 2.442× 10-15, and the MQ-137 sensor is 1.554× 10-15, which means that the data reading from each gas sensor is unstable, less accurate, or unreliable compared to secondary data. However, the designed E-Nose tool can work well and improve farmers' performance in their daily work.